Dampak Perubahan Pengeluaran Wisatawan Terhadap Pendapatan Rumah Tangga di Indonesia: Pendekatan Structural Path Analysis (SPA) dalam SNSE Indonesia - Endah Saptutyningsih (Economic Journal of Emerging Markets, 2003)
This study aims to analyze and identify the impact of change in tourist expenditure towards the household incomes. The data used in this study was secondary one, especially from the Sistem Neraca Sosial Ekonomi (SNSE) Table of Indonesia in 1999 and from tourist expenditure data. The problems appeared in this study were analyzed by using Structural Path Analysis (SPA).The results of the study show that the change in tourist expenditure in Indonesia, most influence the upper household class in urban area in 1999. The change in tourist expenditure most influence non-farm household. Since higher proportion of tourist expenditure is spent to buy non-agriculture products. The urban household receives the influence of change in tourist expenditure more than the rural household. Thus, it is suggested that the government should put emphasis in developing rural tourism by promoting tourism based on agriculture and rural life.Keywords: tourist expenditure, household income, SNSE, Structural Path Analysis (SPA).